Chromatographic separation and identification of fatty acids and phenolic compounds from the seeds of Citrullus colocynthis L. schrad plant growing in Iraq - Bilal, Safaa M.; Khorsheed, Ayad C. (Journal of Kerbala for Agricultural Sciences, 2022)
The current research was presented the phytochemical composition of Citrullus colocynthis schrad seed extracts and it was aimed of the separation and identification of fatty acids from this plant by using a continuous soxhlet apparatus and sequence solvent systems depending on the polarity , the extracts hexane (CI1) ,chIoroform (CI2), ethyl acetate (CI3), ethanol (CI4) and hot aqueous (CI5) were obtained from this seeds and saponification process was done to obtain the free fatty acid compounds ( palmatic, stearic, oleic, linoleic and elaidic acids ). The increasing of concentrations of fatty acid compounds was appeared from CI5 to CI1 because of decreasing of the polarity. Also, the extracts (CI3, CI4 and CI5) were carried out by the acid hydrolysis process to get the free phenolic compounds, which were identified by HPLC technique. The phenolic compounds, which were appeared in C. colocynthis Schrad seed extracts (Rutin , Caffeic acid , Ellagic acid , Gallic acid , Quercetin , Myricetin , Luteolin). Rutin and ellagic acid were appeared in the extracts ( CI3,CI4 and CI5) .Also Caffeic acid and Gallic acid was identified in CI3 and CI4 , while Quercetin and Myricetin were showed in CI4 and CI5. Finally Luteolin was only appeared in CI5.